2010
DOI: 10.1029/2010gc003231
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of preexisting oceanic crust through intraplate igneous activities in the Marcus‐Wake seamount chain

Abstract: [1] Multichannel seismic reflection studies and seismic refraction surveys with ocean bottom seismographs in the Marcus-Wake seamount chain in the northwestern Pacific Ocean reveal P wave velocity structures of hot spot-origin seamounts and adjacent oceanic crust. Inside the seamounts are central high-velocity (>6.5 km/s) structures extending nearly to the top that may indicate intrusive cores. Thick sediment layers (up to 4 km) with P wave velocities of 4-5 km/s have accumulated on seafloor that predates seam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 103 publications
2
40
0
3
Order By: Relevance
“…In addition, most seismic refraction lines performed in previous studies did not reach the required offsets. Kaneda et al (2010) found deeper reflectors at a depth of 35 to 45 km beneath seamounts with a hot spot origin in the northwestern Pacific Basin. They inferred that these reflectors indicate structures that formed via intraplate igneous activities, such as at the top of a mantle partial melting zone or a remnant of a hot spot plume head.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most seismic refraction lines performed in previous studies did not reach the required offsets. Kaneda et al (2010) found deeper reflectors at a depth of 35 to 45 km beneath seamounts with a hot spot origin in the northwestern Pacific Basin. They inferred that these reflectors indicate structures that formed via intraplate igneous activities, such as at the top of a mantle partial melting zone or a remnant of a hot spot plume head.…”
Section: Discussionmentioning
confidence: 99%
“…A recent seismic survey was conducted along the Marcus‐Wake seamount chain [ Kaneda et al ., ], where its associated volcanic edifice was emplaced on a super plume environment in the northwest Pacific basin. Their main results are high‐velocity, intrusive cores at shallow depths and low upper mantle velocities (7.5–8.0 km/s).…”
Section: Interpreting Seismic Imaging Of Deep Crustal Structure At Acmentioning
confidence: 99%
“…One interpretation is that the heterogeneities are remnants of intraplate igneous activities such as the top of a zone of partial mantle melting or part of a hotspot plume head . Kaneda et al (2010) observed reflected waves from depths of 30-45 km beneath the Marcus-Wake seamount chain, and they interpreted the reflectors to have originated from intraplate igneous activity. However, we detected mantle reflectors beneath the normal ocean basin, where crustal thickening due to intraplate volcanism does not occur.…”
Section: Heterogeneity In the Oceanic Lithospherementioning
confidence: 99%
“…Because it is hard to constrain Vp in the mantle, which Pn waves do not penetrate, we extrapolated Vp to the uppermost mantle following the method of Kaneda et al (2010) and Ohira et al (2017b) (Fig. 13).…”
Section: Reflectors In the Oceanic Lithospherementioning
confidence: 99%